PENGARUH AKTIVASI MEREK DAN PENGALAMAN MEREK TERHADAP KESADARAN MEREK DAN KEPUASAN NASABAH ASURANSI JASA RAHARJA DI KOTA PEKANBARU - Primanto, Okto Arif; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2019)
As the current monopoly traffic accident insurance, nowadays JasaRaharja has faced with the discourse of losing its monopoly privilege. Therefore,Jasa Raharja has to make sure that their customers would be highly satisfied. Thisstudy aims to analyze the direct and indirect effect of brand activation and brandexperience toward satisfaction mediated by brand awareness. Population arecustomers who have claimed insurance coverage to Jasa Raharja. The number of96 samples taken by using Slovin and purposive sampling approach. Descriptiveand SEM-PLS employed to analyze the data. The study reveals that brandactivation has significant effect towards brand experience but not significanttowards customer satisfaction. On the other hand, brand experience directlysignificant effect towards customer satisfaction. The mediating role brandawareness is significant on the effect of brand experience towards customersatisfaction, but not significant on the effect of brand activation towards customer satisfaction.